Web-based science lab inventory system for Faculty of Pharmacy in UiTM Bertam / Nurul Farzana Zulkiflee, Siti Fatimah Mohd Rum and Nurisma Ismail - Zulkiflee, Nurul Farzana; Mohd Rum, Siti Fatimah; Ismail, Nurisma (UiTM Cawangan Melaka Kampus Jasin, 2021)
Inventory can be either raw materials, in-process goods, or finished product. Business inventory is always in large numbers therefore to manage and keep track of every inventory; a systematic system is needed to avoid from any shortage or surplus problems. However, university laboratory also such as Faculty of Pharmacy in UiTM Bertam owns an inventory that keeps all apparatus and chemical substances for students’ experiments usage. The process of keeping inventory is still being managed manually. Assistant science officer adds and updates the inventory manually. This can lead to problems like data inaccuracy when adding and updating inventories. Moreover, to use the inventory, lab assistant must fill a form and submit it to assistant science officer, which takes long time to wait for approval. Moreover, there is no notification to notify assistant science officer about expired and low quantity inventory. With these problems, objectives are made that is to gather and analyze requirements from stakeholder, to design and develop Science Lab Inventory System for Faculty of Pharmacy in UiTM Bertam. The system was developed based on the waterfall model that only involved three phases: requirement gathering and analysis, design, and implementation. Each phase has their activities and deliverables done to accomplish the objectives. Interview are conducted with the stakeholder to identify the problems, collect requirements, and documented in Software Requirements Specification (SRS). Diagrams are constructed and documented in Software Design Document (SDD). Subsequently, a web-based system named Science Lab Inventory System for Faculty of Pharmacy in UiTM Bertam is developed